An Empirical Analysis of Buy Now, Pay Later Mechanism and Its Impact on Customer Retention in Digital Commerce (Journal of Entrepreneurship and Business, 2025)
The "Buy Now, Pay Later" (BNPL) mechanism has transformed e-commerce payment systems by providing consumers with enhanced financial flexibility. This study examines the influence of four key factors—interest rate, customer age, credit limit, and income level—on customer retention, aiming to elucidate the relationships among these variables. Utilizing a sample of 385 Malaysian consumers, the study employs both descriptive and inferential statistical analyses. The findings indicate that all four independent variables exert a significant positive impact on customer retention. Specifically, lower interest rates alleviate financial burdens, thereby fostering higher retention rates. Increased credit limits enhance purchasing power and financial flexibility, leading to sustained engagement with BNPL services. Younger consumers exhibit higher retention rates due to their preference for flexible payment solutions, while older users demonstrate consistent BNPL usage, contributing to long-term retention. Additionally, lower-income consumers rely more on BNPL to manage financial constraints, which results in higher retention within this demographic. Notably, usage frequency serves as a significant mediator between customer age and retention, as younger consumers' frequent BNPL usage partially accounts for their elevated retention rates. Conversely, interest rate, credit limit, and income level directly influence retention without substantial mediation by usage frequency. These findings provide valuable insights for e-commerce platforms and policymakers in optimizing BNPL frameworks to accommodate diverse consumer segments and enhance long-term customer loyalty.
Keywords: Array; Array; Array; Array; Array